A market-oriented hierarchical framework for residential demand response. (July 2015) - Ali, Mubbashir; Alahäivälä, Antti; Malik, Farhan; Humayun, Muhammad; Safdarian, Amir; Lehtonen, Matti
Highlights: A two-stage residential framework focusing on DR capability in balancing markets. The DR framework is optimized using a robust optimization approach. Beneficial for both customer and electric aggregator under the smart grid context. Abstract: The integration of a great deal of uncertain renewable sources in future grids will require more operational flexibility. Demand response (DR) can provide the load shaping potentials thereby assuaging the need for operational flexibility. To this end, this paper intends to develop a framework focusing on realization of domestic storage space heating DR capability in balancing market. The developed framework consists of two hierarchical stages named energy market stage and balancing power market stage. The first stage deals with customers' day-ahead decisions in energy market. In this stage, the system operator releases day-ahead energy prices in response to which customers optimize their electricity usage to minimize their energy expenses. The second stage optimizes customers' intra hour load scheduling decisions in balancing power market. In the second stage, up/down power regulation incentives are offered to customers who, in the hope of achieving monetary gains, modify their promised day-ahead decisions. Performance of the framework is verified through simulations on Finnish case studies. According to the obtained results, the framework allows the customers to make savings in energy expenses as well as the system operator to benefit from DR.